Kinematics and kinetics of swing leg in curved sprint running - Ishimura, K.; Sakurai, S. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to demonstrate kinematics and kinetics of left and right swing legs in curved sprint running. Nine male sprinters and decathletes participated in this study. Participants run 60 m on a curved path and their motion was recorded by a motion capture system. The joint angle, angular velocity, moment and power of both swing legs were calculated. For the statistical test, a statistical parametric mapping was used. There were no kinematic and kinetic differences in the hip joint. However, asymmetries were found in the knee joint. Runners may just move swing legs same as for straight running/sprinting.